È solo la lingua che fa eguali. Don Lorenzo Milani sacerdote e maestro - Bruna Bocchini Camaiani (Firenze University Press, 2018)
Don Lorenzo Milani (1923-1967) was an exceptional figure in Italy's Church of the 1950s and 1960s. Italy's new democracy - he believed - needed citizens educated in a new way and the Church new devotees with a minimum of logical and linguistic capabilities. The loss of influence of the Church was not a consequence of Communist propaganda but of widespread ignorance and illiteracy in the population and of inadequate formation of the priests themselves. His famous 'Letter to a teacher', a manifesto for the generation of '68, represents only a minimal part of his pedagogical views that merit to be studied and rediscovered in their richness and completeness.